2016
DOI: 10.1007/s40509-016-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Particle model from quantum foundations

Abstract: Some ideas are explored concerning the structure of elementary particles (specifically, leptons and hadrons), formulated within the context of a theory of the objective collapse of the wavefunction recently proposed by the authors. In accordance with this hypothesis, to each interaction that induces a discontinuity (quantum jump) in the evolution of the state of an elementary particle, two de Sitter half-spaces are associated, respectively, connected with the outgoing state and its conjugate. It is in these sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Elementary RS processes of creation/annihilation of virtual particle/antiparticle pairs corresponding to elementary fluctuations of the quantum vacuum energy density generate oscillations (9) of the vacuum which are choregraphed in a non-local way by the quantum potential of the vacuum. Under opportune conditions, when the region of space is characterized by a certain polarization expressed by the complex unit vector^, they can give rise to the minimum quantum of the electromagnetic field, which can be characterized in terms of the quantized vector potential (17) satisfying the wave equation (19), the linear time differential equation (20), and the Schrödinger equation (21), which can be thus combined into a wave-particle general equation (22). It implies that the photon is a "wave-corpuscle" entity emerging from more fundamental properties of the non-local 3D quantum vacuum which is a perfect absorber and emitter.…”
Section: From the Reduction-state Processes Of Creation/annihilation mentioning
confidence: 99%
See 3 more Smart Citations
“…Elementary RS processes of creation/annihilation of virtual particle/antiparticle pairs corresponding to elementary fluctuations of the quantum vacuum energy density generate oscillations (9) of the vacuum which are choregraphed in a non-local way by the quantum potential of the vacuum. Under opportune conditions, when the region of space is characterized by a certain polarization expressed by the complex unit vector^, they can give rise to the minimum quantum of the electromagnetic field, which can be characterized in terms of the quantized vector potential (17) satisfying the wave equation (19), the linear time differential equation (20), and the Schrödinger equation (21), which can be thus combined into a wave-particle general equation (22). It implies that the photon is a "wave-corpuscle" entity emerging from more fundamental properties of the non-local 3D quantum vacuum which is a perfect absorber and emitter.…”
Section: From the Reduction-state Processes Of Creation/annihilation mentioning
confidence: 99%
“…(17)-(23), a fundamental result is the following. Although when frequency (9) is null, all the physical properties of a photon vanish, it must be observed that, even if = 0, the field Ξ Δ appearing in (17) is not null and becomes the vacuum field Ξ 0 involving the polarization and generating the electronic transitions in matter. This is a fundamental point: this physically means that, when a region of the 3D quantum vacuum is described by the quantized vector potential (17) satisfying the fundamental wave-particle equation (22), this region of the vacuum becomes a source of physical (electromagnetic) processes, even if frequency (9) of this region becomes null.…”
Section: From the Reduction-state Processes Of Creation/annihilation mentioning
confidence: 99%
See 2 more Smart Citations
“…Before going on, let us consider T0, a sort of "internal period" of the origin x = 0 of the frame of reference; for the connection of T0 with T1 we will return later on. Here, we hypothesize that in the Archaic Universe the origin of a frame of reference is endowed with a finite extension in x0/c equal to q0, a typical scale of the temporal localization of elementary particles [8][9][10][11][12][13][14]. The random choice of a particular origin on the x0/c axis thus corresponds to an a priori probability equal to the ratio q0/t0 between the interval q0 and the extension of the x0/c axis, and an information 1/a = -log2(q0/t0).…”
Section: "Archaic" Origin Of the Inertia Principle (And Its Violation)mentioning
confidence: 99%